2021
DOI: 10.3390/ijerph182212255
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor in Family Tobacco Farms in Southern Brazil: Occupational Exposure and Related Health Problems

Abstract: Tobacco farming is considered Hazardous Child Labor in Brazil. This study examined the work of children and adolescents in tobacco farming, characterizing the level of urinary cotinine and the occurrence of Green Tobacco Sickness (GTS), pesticide poisoning, respiratory symptoms, and musculoskeletal disorders. A cross-sectional descriptive study was conducted with a random sample of tobacco growers under 18 years old in Southern Brazil. Ninety-nine young people were interviewed at 79 family farms. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…For those interviewed, ~ 60% were 16-17 years old, and 51.5% were male. During their lifetime, ~ 25% reported GTS, and 3% pesticide poisoning 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For those interviewed, ~ 60% were 16-17 years old, and 51.5% were male. During their lifetime, ~ 25% reported GTS, and 3% pesticide poisoning 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have found that children working in dangerous jobs experience health problems such as respiratory system diseases, musculoskeletal system disorders and injuries, poisoning, fractures, and dislocations (Batomen Kuimi et al., 2018; Fassa et al., 2021; Quandt et al., 2019). A systematic review examining child waste workers found the most common health problems experienced by child workers were musculoskeletal and respiratory system problems (Sara et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it may fail to capture people who are less exposed to certain risks, such as pesticides. Additionally, since working with pesticides and in tobacco farming is prohibited for individuals under 18 years of age and older adults, some families do not report when people in these age groups are regular workers, leading to a selection bias 22 . Some studies that assess chemical exposure target pesticide applicators, investigating those who were applicators in the last year or the last crop season to capture the most exposed individuals 10 .…”
Section: Rural or Agricultural Workermentioning
confidence: 99%
“…Legal restrictions on child labor also hinder identifying and conducting interviews with agricultural workers under the age of 18. When this is a group of interest, it is recommended to include all residents of the establishment and assess their participation in agricultural activities during the interview 22 . In studies on family farming, reconciling the economic characterization is also challenging.…”
Section: Definition Of Interviewees: Owner Family And/or Employeesmentioning
confidence: 99%